A validated reverse phase HPLC method for the simultaneous estimation of clopidogrel bisulfate and rivaroxaban in pharmaceutical application - Sajjanwar, Rupali; Bhaskaran, Shyamala; Kakati, Kulesh; Jha, Shailendra Kumar (Journal of Applied Pharmaceutical Research, 2015)
A simple, sensitive and precise reverse phase high performance liquid chromatographic method has been developed for the simultaneous estimation of Clopidogrel bisulfate and rivaroxaban in pharmaceutical dosage forms. The combination drug was analyzed on BDS hypersil C18, 250mm Ãâ 4.6mm, 5ÃÂµ, Thermo scientific. Mobile phase consisted ofÃÂ  buffer (0.05M KH2PO4 pH 4.0) : methanol in the ratio of 30:70 v/v delivered at a flow rate of 1.0 ml / min and wavelength of detection at 220 nm. The retention times of Clopidogrel bisulfate and Rivaroxaban were 2.39 min and 4.04 min respectively. The developed method was validated according to ICH guidelines. The proposed method can be used for the determination of these drugs in combined dosage forms.